After Iraq: New hope for Kashmir? - Christian Wagner; Boris Wilke (Stiftung Wissenschaft und Politik (SWP), 2003)
Indian Prime Minister Atal Behari Vajpayee's visit to Berlin in May and Pakistani President General Pervez Musharraf's upcoming trip to Germany come at a time of rapprochement between India and Pakistan. With their new initiative to reassume talks, the governments in New Delhi and Islamabad are responding to pressure from the United States, which palpably increased in the aftermath of Washington's successful campaign in Iraq. For the U.S. administration, the Kashmir conflict between India and Pakistan is the most important regional trouble spot besides the Middle East and North Korea. The U.S. apparently has its sights set on a permanent settlement between India and Pakistan of the Kashmir dispute . However, India and Pakistan have reacted somewhat reluctantly to this policy. India has always rejected official mediation in Kashmir. And although Pakistan had previously attempted to internationalise the conflict, the country is now nervous about possible American involvement, which, in the long term, could call into question the country's possession of nuclear weapons. (SWP Comments / SWP)
Keywords: 320